KOMPOSISI ANGGREK TANAH DAN VEGETASI LANTAI HUTAN DI JALUR PENDAKIAN UTAMA GUNUNG ANDONG, MAGELANG, JAWA TENGAH - Siti Aisah; Ita Rosita Istikomah (Kaunia: Integration and Interconnection Islam and Science, 2014)
Due to the risk ofwildtype orchids extinction, studies on the diversity of orchid species are important. Generally, floral checklist can be used to describe plant diversity such as terrestrial orchid species and  forest floor vegetation.This research was aimed to know terrestrial orchid species  & forest floor vegetation at Gunung Andong, Magelang, Jawa Tengah. Field research was done by exploration method using purpossive sampling at main tracking route of Gunung Andong and data analysis was calculated based on vegetation parameters i.e. plant density and frequency. The result showed that there are 24 species of terrestrial plants belongs to 4 subfamilia: Orchidoideae, Epidendroideae, Cypripedioideae, and Spiranthoideae. Also, this research has found 52 species of 24 familia of forest floor vegetation. Based on the composition of terrestrial orchids and forest floor vegetation, we assume that the plant diversity at Gunung Andong, Magelang, Jawa Tengah is relatively high and routine  monitoring is needed.